The Power of the influencer - the possibilities of using social media to develop the Namibian fashion industry (Namibian Journal of Linguistics, Literature and Communication Studies, 2024)
This article explores how social media can be used as a tool to develop the nascent Namibian fashion industry and encourage consumer interest. This research started from the hypothesis that a localised social media platform could be used as a tool to boost industry competitiveness as well as consumer support. The research took on a mixed methods approach where a survey was undertaken, followed by a series of interviews of local fashion industry stakeholders to gain insight into how social media could best serve Namibian fashion. Analysis of results indicates that a localised social media platform could be beneficial for the industry but it is important that such a platform not exclude opportunities of international exposure and networking. Furthermore, for such a platform to work, stakeholders in the Namibian fashion industry will have to embrace the power of influencers on social media, and the idea of ‘co-creation’ with the social media audience.
Keywords: social media; fashion; innovation; industry development; namibia